STRATEGI KOMUNIKASI ANTARPRIBADI DOSEN DAN MAHASISWA DALAM PENGEMBANGAN JIWA KREATIF - Rama Kertamukti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
This research limited to pattern strategy Human relation communication lecturers and students course of study Science Communication UIN Sunan Kalijaga Yogjakarta in development creativity. The subject of study is lecturers in communication science department and object his research is development creativity students in course of study Science Communication UIN Sunan Kalijaga. Researchers want to uncover and analyzes result of data obtained during this observation and interview supported with the data which reduced of library.In Human relation communication interaction between lecturer with students expressing things that can be handled to talk about mental development in creative students. Research results, communication science department UIN Sunan Kalijaga always trying to establish communication human relation with students in every opportunity. The various methods and strategies for learning lessons done to improve and develop creative spirit a student. Human relation communication holds a very important role in development strategies creativity. These communication patterns are able to develop creativity students, because in addition to the student got the pattern supervision lecturer for active and always communicate with the lecturer and with his friend, either while in college and while completing coursework so intertwined processes of interaction and transactions between lecturers and students.